METHODS OF STABILIZATION OF DRUG SUBSTANCES AND THEIR METABOLITES IN BIOLOGICAL FLUIDS DURING BIOANALYTICAL STUDY (REVIEW) - I. I. Yaichkov; A. L. Khokhlov; Y. A. Dzhurko; L. N. Shitov; A. A. Trubnikov (Разработка и регистрация лекарственных средств, 2019)
This article describes main methods of preventing degradation of chemically unstable drugs and their metabolites in biological fluids during storage after collection from patients. It is necessary for accurate quantitative determination of these compounds.